Analisis khiyar majlis pada transaksi e-commerce live streaming: Perspektif fikih mazhab Syafi’i-Maliki - Ramadhan, Rahmat Gilang (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
The rise of live streaming-based e-commerce has transformed modern trade practices, introducing new challenges in applying Islamic legal principles such as khiyar majlis. This principle allows both seller and buyer to choose whether to proceed with or cancel a transaction while they remain in the same session (majlis). In digital contexts, however, the concept of a majlis becomes unclear, prompting differing interpretations among scholars. This study analyzes the applicability of khiyar majlis in live streaming e-commerce from the perspectives of the Syafi’i and Maliki schools. The Syafi’i view supports the continued validity of khiyar majlis in digital spaces as long as the interaction persists. Conversely, the Maliki school does not recognize khiyar majlis in the absence of direct, physical meetings. Using a descriptive-analytical method, this research examines the relevance of khiyar majlis to consumer protection and fairness in digital transactions. The findings suggest that khiyar majlis can still be implemented in digital commerce, provided the process ensures transparency and protects both parties’ rights.